Association between Systemic Lupus Erythematosus and Refractory Ulcerative Colitis: What are our Therapeutic Options? (Global Journal of Medical Research, 2023)
Systemic lupus erythematosus SLE is an autoimmune disease in which the immune system through antibodies attacks its own tissues and causes inflammation and tissue damage in the affected organs It can affect the skin brain lungs kidneys and blood vessels 1 Ulcerative colitis is an inflammatory bowel disease IBD that causes inflammation and ulcers sores in your digestive tract Ulcerative colitis affects the innermost lining of your large intestine also called the colon and rectum This article is about a patient followed for systemic lupus presenting digest if symptoms reveling ulcerative colitis the therapeutic challenge we faced is the potential aggravation of lupus symptoms under anti TNF therapy The patient underwent curative surgery without major complication